HOW CAN BLOCKCHAIN IMPROVE EMPLOYEE PERFORMANCE? - Zora Calista Susilo; Tito Wira Eka Suryawijaya; Santi Isnaini; Thant Thet Oo (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
Entering the era of the Internet of Things (IoT), one of the main challenges faced by human resources (HR) departments related to human resource management information systems (HRIS) is employee data security and process efficiency which can affect overall organizational productivity. The aim of this research is to provide companies with an in-depth understanding of the potential and implications of using blockchain technology in human resource management information systems (HRIS) and its impact on employee performance. This study uses a quantitative approach with the survey method. The research population comes from HRD professionals who work in companies at various company levels in all industrial fields in the Java-Bali region.PData collection uses an online questionnaire with an interval scale.There were 350 samples taken by purposive sampling and tested using the Partial Least Squares method. Research resultshow that adoption of blockchain technology modifies the relationship between key human resource management variables, such as job satisfaction, transparency, work culture, and work motivation, with employee performance, revealing complex dynamics that require a deeper understanding in dealing with technological developments. This research has limitations in taking respondents because the number taken as samples is still relatively small, namely only in the Java-Bali regions and the variability of the data is still not balanced in terms of sex, length of work and company level. Thus, this research does not just explore the relationship between variables,However also presents findings that provide deep insight into the role of blockchain technology in the transformation of human resource management.